Engaging Faculty in an Evaluative Conversation. Issue 151 (September 2016) - Rickards, William H.; Abromeit, Jeana; Mentkowski, Marcia; Mernitz, Heather
Abstract: Higher education evaluation or assessment plans generally look to key assessments within the curriculum for critical demonstrations of students' learning. Increasingly, accreditation agencies (e.g., Southern Association of Schools and Colleges, National Council on Accreditation of Teacher Education) have asked for evidence of how faculty have made use of student outcome data in their own ongoing planning. This is a condition that expands the notion of evaluation as a collection of data from which to examine the merit or worth of a program to the collaborative and analytic meaning making of evaluative action. This has been an area of traditional complication where evaluators work to support the use of evaluation findings while maintaining appropriate independence from the program administrators with operational responsibility. However, this combination of instructional needs, accountability expectations, and insight into evaluative outcomes amplifies the need for evaluator expertise for collaborating in these dimensions of practice. This study then examines the work of a faculty and its assessment team—including evaluation researchers—to (a) implement and evaluate a general education program through a midprogram assessment, (b) analyze the faculty's engagement with the results and (c) adapt the reporting and meaning‐making processes to further invest the faculty as coinvestigators in the evaluation and its use in improving the program.